2015
DOI: 10.1016/j.geoderma.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application does not improve the soil hydrological function of a sandy soil

Abstract: a b s t r a c tBiochar application to soil is currently being widely posited as a means to improve soil quality and thereby increase crop yield. Next to beneficial effects on soil nutrient availability and retention, biochar is assumed to improve soil water retention. However, evidence for such an effect in the primary literature remains elusive. Therefore, we studied the effect of biochar on soil hydrological characteristics in two separate field experiments on a sandy soil in The Netherlands. In Experiment I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(186 citation statements)
references
References 40 publications
14
151
2
3
Order By: Relevance
“…This is in agreement with Jeffery et al [33], who did not observe either a biochar effect on water retention nor differences between the biochars at 400 • C and 600 • C, despite the biochar 600 • C having higher porosity. Although temperature of pyrolysis is considered the most important factor determining physical changes of biochar, feedstock type determines the temperature range under which changes occur [15].…”
Section: Biochar Contribution To Soil Water Retentionsupporting
confidence: 93%
“…This is in agreement with Jeffery et al [33], who did not observe either a biochar effect on water retention nor differences between the biochars at 400 • C and 600 • C, despite the biochar 600 • C having higher porosity. Although temperature of pyrolysis is considered the most important factor determining physical changes of biochar, feedstock type determines the temperature range under which changes occur [15].…”
Section: Biochar Contribution To Soil Water Retentionsupporting
confidence: 93%
“…Authors such as Novak et al (2012), Carvalho et al (2014) and Sun and Lu (2014) evidenced the increase in available water in the soil, as well as the improvement in its retention with biochar application. Studies conducted by Major et al (2012) and Jeffery et al (2015) did not show significant results with the application of biochar in the soil as an alternative of water use efficiency. It is believed that the influence of the use of biochar in the increase of water availability is related to the applied dose and the morphological characteristics of the soil, such as mineralogy and granulometry (TEIXEIRA et al, 2017).…”
Section: Resultsmentioning
confidence: 85%
“…Other studies have demonstrated the lack of positive results in this aspect (MAJOR et al, 2012;JEFFERY et al, 2015), while others have observed limitations in water availability (TEIXEIRA et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…The biochar produced at high temperatures possesses pores unclogged by volatile/mobile matter and converts the biochar surface to be more hydrophilic [71]. However, Jeffery et al [72] reported no significant impact on soil water retention and K sat after the application of hay biochar produced at 400 and 600 • C to sandy soil.…”
Section: Resultsmentioning
confidence: 99%